PELATIHAN PENGGUNAAN E-DRAW MAX UNTUK MEMBUAT DESAIN SISTEM - Tundo Tundo; Andi Saidah (Universitas 17 Agustus 1945 Jakarta, 2023)
Edraw Max is a 2D business technical diagram software that helps create flowcharts, organization charts, mind maps, network diagrams, floor plans, workflow diagrams, business charts and Engineering diagrams, flowcharts, graphs and mappings, besides E- Draw Max is also a vector-based diagramming software, which is usually used to make it easier to make a design. One of them is the design of a production process system in a factory that can use this application. In this training, the E-Draw Max tools will focus on making Data Flow Diagrams (DFD), which are useful for describing the flow of the created system, which consists of Context Diagrams, Level Diagrams, and Level n Diagrams. Data Flow Diagram (DFD) is a diagram that describes the flow of data from a process or information system. In DFD, there is information related to the input and output of each of these processes. DFD also has various functions, such as conveying system design, describing systems, and designing models. This training was held at the ITS NU Pekalongan Institute of Computer Technology. The purpose of this training is to help ITS NU Pekalongan S1 Computer Technology students in making system designs, specifically designing Data Flow Diagrams (DFD) using E-Draw Max tools to make it easier for students to make the flow of the system made in this case DFD on production process in Industry.